Radiation from an open ended eccentric annular waveguide - Ragheb, H.A. (1997)
The radiation from an open ended eccentric annular waveguide is examined here. The region between the two circular conductors is assumed to have either symmetrical or anti-symmetrical TE field distribution. The cut-off wavenumber is first calculated and the unknown coefficients in the field are then obtained. It is found that for anti-symmetric field distribution the radiation pattern in the H-plane has a null which can be widely scanned by displacing the conducting core from the central axis. For the symmetrical field distribution a pair of symmetrical nulls in the E-plane are slightly scanned with the displacement of the conducting core. This type of waveguide antenna is useful for applications in phased and adaptive arrays which require null scanning